Costs and resource needs for primary health care in Ethiopia: evidence to inform planning and budgeting for universal health coverage - Alebachew, Abebe; Abdella, Engida; Abera, Samuel; Dessie, Ermias; Mesele, Tesfaye; Mitiku, Workie; Muñoz, Rodrigo; Opuni, Marjorie; Teplitskaya, Lyubov; Walker, Damian G.; Gilmartin, Colin (Frontiers in Public Health, 2023)
Introduction The Government of Ethiopia (GoE) has made significant progress in expanding access to primary health care (PHC) over the past 15 years. However, achieving national PHC targets for universal health coverage will require a significant increase in PHC financing. The purpose of this study was to generate cost evidence and provide recommendations to improve PHC efficiency. Methods We used the open access Primary Health Care Costing, Analysis, and Planning (PHC-CAP) Tool to estimate actual and normative recurrent PHC costs in nine Ethiopian regions. The findings on actual costs were based on primary data collected in 2018/19 from a sample of 20 health posts, 25 health centers, and eight primary hospitals. Three different extrapolation methods were used to estimate actual costs in the nine sampled regions. Normative costs were calculated based on standard treatment protocols (STPs), the population in need of the PHC services included in the Essential Health Services Package (EHSP) as per the targets outlined in the Health Sector Transformation Plan II (HSTP II), and the associated costs. PHC resource gaps were estimated by comparing actual cost estimates to normative costs. Results On average, the total cost of PHC in the sampled facilities was US 11,532 (range: US 934–40,746) in health posts, US 254,340 (range: US 68,860–832,647) in health centers, and US 634,354 (range: US 505,208–970,720) in primary hospitals. The average actual PHC cost per capita in the nine sampled regions was US 4.7, US 15.0, or US 20.2 depending on the estimation method used. When compared to the normative cost of US 38.5 per capita, all these estimates of actual PHC expenditures were significantly lower, indicating a shortfall in the funding required to deliver an expanded package of high-quality services to a larger population in line with GoE targets. Discussion The study findings underscore the need for increased mobilization of PHC resources and identify opportunities to improve the efficiency of PHC services to meet the GoE’s PHC targets. The data from this study can be a critical input for ongoing PHC financing reforms undertaken by the GoE including transitioning woreda-level planning from input-based to program-based budgeting, revising community-based health insurance (CBHI) packages, reviewing exempted services, and implementing strategic purchasing approaches such as capitation and performance-based financing.